Preparation of Tyramine-molecularly Imprinted Materials and Its Research Progress in Food Detection - Ding YANG; Yuanyuan HUI; Weizhe WANG; Yingying LIU; Chao HE; bini WANG (Shipin gongye ke-ji, 2023)
Tyramine (TYR) is a bioactive organic compound with low molecular weight containing nitrogen. It is found in fermented or preserved foods, aged cheeses, beer, fruits, cured meats and dried meats, and is a by-product of microbial activities. It will produce greater harm to the human body, when the concentration is high. Therefore, sensitive and rapid detection of TYR content in food and control of its generation and accumulation is a hot issue concerned by the food industry. Current techniques for accurate detection of TYR include polymerase chain reaction technique and enzyme-linked immunosorbent assay, but both suffer from long detection cycle and cumbersome operation, which are not suitable for rapid detection of TYR in the field. The imprinted polymers prepared by molecular imprinting technology are highly selective and specific for the target with high stability, and have a wide range of applications, and thus are favored by researchers at home and abroad. In this paper, the preparation methods of tyramine-molecularly imprinted materials are introduced, including bulk polymerization, in-situ polymerization, sol-gel method and electrochemical polymerization. The latest research progress of molecularly imprinted technique for TYR detection in food in recent years is reviewed, such as the combination with solid-phase extraction, electrochemical sensors, fluorescent sensors and mass sensors and the future development prospects of molecular imprinting technology in the detection of TYR are prospected, which provides a certain basis for future research work.